Intrusions propagating into linearly stratified ambients. (13th April 2018) - Khodkar, M. A.; El Allam, K.; Meiburg, E.
Abstract : Equilibrium and non-equilibrium intrusions released from long, full-depth locks and advancing into linearly stratified ambients are investigated via a vorticity-based modelling approach, for the constant-velocity slumping phase. Non-equilibrium intrusions give rise to an upstream-propagating wave, which we model as a bore. Predictions by the vorticity model agree closely with two-dimensional direct numerical simulation results and earlier experimental and computational data regarding front velocities, current thicknesses as well as the height and propagation velocity of the bore.